Efficacy of Wenxin Keli Plus Amiodarone versus Amiodarone Monotherapy in Treating Recent-Onset Atrial Fibrillation - Nixiao Zhang; Gary Tse; Shristi Dahal; Yajuan Yang; Mengqi Gong; Calista Zhuo Yi Chan; Enzhao Liu; Gang Xu; Konstantinos P. Letsas; Panagiotis Korantzopoulos; Guangping Li; Tong Liu (Cardiology Research and Practice)
Background. Use of amiodarone (AMIO) in atrial fibrillation (AF) has significant side effects over prolonged periods. Wenxin Keli (WXKL), a Chinese herb extract, has been shown to be effective in atrial-selective inhibiting peak INa and hence beneficial in treating atrial arrhythmias, including atrial fibrillation. The aim of this randomized controlled trial was to evaluate potential effects of AMIO plus WXKL on conversion rate and time in patients with recent-onset AF. Methods. A total of 41 patients (71 ± 12 years, 44% male) with recent-onset (<48 h) AF eligible for conversion were randomized to receive either intravenous amiodarone (loading dose 5 mg/kg in 1 hour followed by 50 mg/h; n=21) or amiodarone with same dosage plus oral WXKL 18 g thrice daily (n=20) for 24 hours. Results. Conversion rate at 24 hours was of no difference between the two groups (75.0% vs. 81.0%, P=0.72); however, conversion time was markedly shorter in the AMIO + WXKL group compared to the AMIO group (291 ± 235 minutes vs. 725 ± 475 minutes, P=0.003). There were no serious adverse events during the study. Conclusion. Administration of amiodarone plus WXKL for recent-onset AF conversion was safe and effective, with faster sinus rhythm restoration compared with amiodarone alone.